Studying the effect of thermal fatigue on multiple cracks propagating in an SS316L thin flange on a shaft specimen using a multi-physics numerical simulation model - Mukhta, Fariha (Strojniški vestnik, 2019)
After more than a decade of research on thermal fatigue cracking in nuclear reactor components, the science remains incomplete. It is essential to understand the crack propagation behaviour and the influence of multiple cracks on the fatigue life of a component due to thermal fatigue load. Accurate numerical simulation modelling can help in better understanding the influence of different factors on failure propagation. In this research, a finite element-based numerical simulation model has been developed using ABAQUS commercial software to obtain insight into crack propagation and crack arrest in an SS316L thin flange on shaft specimen; the assembly is cooled internally, and cyclic thermal loading is applied on the flange rim. The experiment was carried out on a specially designed rig using an induction coil for heating the outer rim. Thermocouples were attached radially on the rim to collect detailed temperature profiles. Real-time temperature-dependent elastic-plastic material data was used for modelling. The boundary conditions and thermal profile used for the numerical model were matched with experimental data. The stresses responsible for crack initiation, the effect of crack number and crack lengths on stresses, energy absorbed at the crack tip after every thermal cycle and the threshold values of cracks are evaluated in the current work. The obtained simulation results were validated by comparing experimental observations. The developed simulation model helps in better understanding the evolution of stresses and strains in uncracked and cracked SS316L discs mounted on a flange due to thermal cycling. It also helped in better understanding the crack propagation behaviour and the evolution of energy release at crack tips. Such a model can help future researchers in designing components undergoing thermal fatigue loading, for example, in nuclear power plants.
Keywords: crack propagation; hoop stress; J- integral; J-integral; napredovanje razpoke; numerical simulation; numerična simulacija; obodna napetost; SS316L; thermal fatigue; toplotno utrujanje